EMPOWERMENT OF HOME MICRO CAKE BUSINESSES IN GAMPONG BLANG PULO - Dy Ilham Satria; Muhammad Yusra; Rani Gesta Putri; Hilmi; Jubaidah; Atika Salsabila (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The problems faced by home cake micro business partners are; 1) The production aspect consists of limited production equipment so that it takes a long time to fulfill large orders, simplicity of production equipment and equipment so that it cannot produce quality products, especially for dry cakes. 2) Aspects of financial management and marketing consist of the absence of business financial reports so that partners cannot measure business development, and there is no product packaging that attracts consumers to buy. The aim of this activity is to find solutions to the problems faced by the home cake making micro entrepreneur partners that the PKM Team runs in the community service program, through mentoring, and training and procurement of household industrial scale mixer and oven equipment, assistance in making financial reports, and designing attractive product packaging. The method or approach offered and agreed upon with the micro entrepreneur partners who make Dry Cakes and Wet Cakes is training and assistance as well as procuring equipment and designing hygienic and attractive packaging for dry cakes and cakes products, as well as providing assistance in making Financial Reports. The planned output targets to be achieved by the PKM team are mandatory outputs in the form of; Service Reports, Publication of articles in OJS-based service journals or national seminar proceedings, Publication of activities in print or online media, and Collaboration Documents with partners, as well as IPR in the form of Copyright.